A Simplified Analysis Model for Predicting the Crack Width and Deflection of Reinforced UHPC Shallow T-Shaped Beams Under Four-Point Bending - Zhe Zhang; Yichuan Wang; Binchen Yuan; Ping Zhu (Buildings)
To predict the mid-span deflection and crack width of reinforced ultra-high-performance concrete (R-UHPC) shallow T-shaped beams, a simplified analysis model comprising a bilinear curve with several characterization points is proposed in this paper. The proposed model is distinguished from existing deflection and crack width prediction methods by its consideration of several significant factors, including the tensile stiffening effect, tension contribution of UHPC post-cracking, nonconstant bond behavior of the interface, and shrinkage and creep effect. To obtain closed-form solutions, the proposed simplified analysis model directly incorporates the bond properties from bond tests, thereby eliminating the reliance on constant bond stress simplification and the subsequent necessity for member calibration, which is commonly required in existing design codes for UHPC-based structures. To validate the proposed model, six reinforced UHPC shallow T-shaped specimens with dimensions of 3.7 m × 0.7 m × 0.22 m, varying reinforcement ratios and fiber types within UHPC, are utilized and tested statically under four-point bending conditions. The experimental values obtained from these tests are then compared with the theoretical calculations derived from the simplified analysis model. The ratios of mid-span deflections and crack widths at reinforcement yielding, calculated using the simplified analysis model, to the counterparts from experimental values are found to be within a range of 0.9 and 0.95, respectively. The average percentage of differences between experimental and predicted values for the deflections and crack widths at reinforcement yielding are 4.2% and 5.8%, respectively. These findings demonstrate that the simplified analysis model proposed is accessible and accurate for predicting the deflection and crack width of reinforced UHPC shallow T-shaped beams, which has the potential to be a valuable reference for the design and calculation of such beams.